Regulation of proliferation-associated leucine-rich protein 31 in the rat ovary - Cheung, Carmen K. M (University of Ottawa (Canada), 2005)
In neuronal and placental cells, proliferation-associated leucine-rich protein 31 is an anti-apoptotic, cell cycle-related protein in its intact form, and upon cleavage by caspase-3, is pro-apoptotic. However, whether PAL31 is expressed in the follicle and is modulated during follicular development and atresia is not known. The expression and regulation of ovarian PAL31 were investigated using immature rat models and a granulosa cell culture system. PAL31 was ubiquitously expressed in all follicular cell types. eCG caused a significant decrease in granulosa cell PAL31 protein content during granulosa cell differentiation and late stage follicle growth. Gonadotropin withdrawal prevented an increase in ovarian weight after eCG treatment, but failed to induce granulosa cell apoptosis and PAL31 cleavage. Finally, estradiol stimulated PAL31 expression in the granulosa cells of preantral and early antral follicles. These results demonstrate for the first time that PAL31 is regulated by key reproductive hormones during follicular development in vivo.
Keywords: Biology, Molecular.; Biology, Cell.; Chemistry, Biochemistry.